Viewpoint: digital paediatrics-so close yet so far away - Hensel, KO; Powell, J (BMJ Publishing Group, 2021)
Technology is driving a revolution in healthcare, but paediatric services have not fully harnessed the potential. Digital health solutions yet to achieve their promise in paediatrics include electronic health records, decision support systems, telemedicine and remote consultations, despite the accelerated uptake during the COVID-19 pandemic. There are also significant potential benefits in digitally enabled research, including systems to identify and recruit participants online or through health records, tools to extract data points from routine data sets rather than new data collection, and remote approaches to outcome measurement. Children and their families are increasingly becoming digital health citizens, able to manage their own health and use of health services through mobile apps and wearables such as fitness trackers. Ironically, one barrier to the uptake of these technologies is that the fast pace of change in this area means the evidence base behind many of these tools remains underdeveloped. Clinicians are often sceptical of innovations which appear largely driven by enthusiasts rather than science. Rigorous studies are needed to demonstrate safety and effectiveness. Regulators need to be agile and responsive. Implementation needs adequate resource and time, and needs to minimise risks and address concerns, such as worries over losing human contact. Digital health care needs to be embedded in medical education and training so that clinicians are trained in the use of innovations and can understand how to embed within services. In this way, digital paediatrics can deliver benefits to the profession, to services and to our patients.